Peningkatan Keterampilan Menyimak Melalui Model Problem Based Learning Pada Siswa Kelas IV SDN 60/II Muara Bungo - Fadilah Fadilah; Aprizan Aprizan; Megawati Megawati (Master Journal of Future Education, 2025)
This Classroom Action Research (CAR) was conducted on fourth-grade students at SDN 60/II Muara Bungo, motivated by their low listening skills, as evidenced by their learning outcomes and the average score of the Indonesian language learning test. Of the 24 students, only 11 completed the course and 13 failed. This indicates continued low student learning outcomes. Therefore, a learning model that can improve students' listening skills is Problem-Based Learning. The purpose of this study was to improve students' listening skills using the Problem-Based Learning model in Indonesian language learning in fourth-grade students at SDN 60/II Muara Bungo. The method used was Classroom Action Research (CAR). The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of this study were 24 fourth-grade students at SDN 60/II Muara Bungo. Data collection used teacher observation sheets, student observation sheets, and test questions. The results obtained from this study include: 1) students' listening skills using the Problem Based Learning model are categorized as good, 2) after the implementation of the Problem Based Learning model, the results and learning processes of students in each cycle have increased above the KKTP value of 70, 3) increasing students' interest and motivation in learning through the application of the Problem Based Learning model. The application of the Problem Based Learning learning model can increase students' activeness and cooperation in learning with the presence of video media displayed which can help students to be more focused and attract students' attention in the learning process, so that it can improve the completeness of student learning outcomes.